2021
DOI: 10.1371/journal.pone.0249353
|View full text |Cite
|
Sign up to set email alerts
|

Upper body rate of force development and maximal strength discriminates performance levels in sport climbing

Abstract: The aim of this study was to assess and compare the maximal force and rate of force development (RFD) between intermediate, advanced and elite climbers using several different methods for calculating RFD. Fifty-seven male climbers (17 intermediate, 25 advanced, and 15 elite) performed isometric pull-ups on a climbing-specific hold while the RFD was calculated using several absolute (50, 100, 150, 200, and 250 ms from onset of force) and relative time periods (25, 50, 75, 95, and 100% of time to peak force). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 32 publications
(90 reference statements)
0
21
2
1
Order By: Relevance
“…The available literature is challenged by the vast variety of applied endurance-, strength-, and power tests (Ozimek et al, 2016;Michailov et al, 2018;Levernier and Laffaye, 2019;Torr et al, 2020;Stien et al, 2021c). For example, this review revealed 13 trials that had implemented the intermittent forearm endurance test, and these provided nine different combinations of work-to-rest ratios and force thresholds (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The available literature is challenged by the vast variety of applied endurance-, strength-, and power tests (Ozimek et al, 2016;Michailov et al, 2018;Levernier and Laffaye, 2019;Torr et al, 2020;Stien et al, 2021c). For example, this review revealed 13 trials that had implemented the intermittent forearm endurance test, and these provided nine different combinations of work-to-rest ratios and force thresholds (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have explored tests measuring the force generated by the upper-body pulling apparatus (arms-and backmuscles) (Levernier and Laffaye, 2019;Stien et al, 2021b,c). Such test set-ups might provide a higher climbing-specificity, but at the expense of reliability as the inclusion of more joints could entail a larger variation in results (Stien et al, 2021c). Using an unconstrained, 90 • elbow angle, Levernier and Laffaye (2019) demonstrated that maximal strength (CV = 2.9-10.0%) and RFD (CV = 7.8-28.3%) assessed standing and with an open-hand grip were reliable and able to discriminate between novice, skilled, and international climbers.…”
Section: Isometric Pulling Testsmentioning
confidence: 99%
See 3 more Smart Citations